Natural compounds in the management of polycystic ovary syndrome: a comprehensive review of hormonal regulation and therapeutic potential - Yuan, Jingyi; Li, Zhenmin; Yu, Yongjiang; Wang, Xiuge; Zhao, Yunyun (Frontiers in Nutrition, 2025)
Polycystic ovary syndrome (PCOS) is a multifaceted endocrine disorder characterized by irregularities in gonadotropin secretion, hyperandrogenism, chronic anovulation, and polycystic ovarian morphology. In addition, it is often associated with metabolic dysfunctions, most notably insulin resistance (IR). This disorder affects approximately 6–20% of individuals, primarily emerging during early adolescence, and considerably increases the risk of conditions such as impaired glucose tolerance, type 2 diabetes, endometrial cancer, cardiovascular diseases, dyslipidemia, and postpartum complications. To date, there is no standardized protocol for treating PCOS. Existing therapies primarily rely on personalized pharmacotherapy and lifestyle modifications. However, these treatments may often lead to adverse effects, and most medications prescribed for PCOS are used off-label and have not secured approval from the U.S. Food and Drug Administration specifically for this condition. Recently, natural compounds have garnered considerable attention due to their efficacy in hormone modulation and minimal toxicity. Substances such as myo-inositol, resveratrol, berberine, and quercetin have shown promise in mitigating PCOS symptoms. Their multi-target properties offer the potential to achieve outcomes unattainable by single-target pharmaceuticals, particularly in managing heterogeneous conditions. This review aims to comprehensively analyze in vivo and in vitro research alongside clinical interventions to evaluate the influence of natural compounds on the prevalence of PCOS and their therapeutic potential. These investigations lay the groundwork for developing innovative therapeutic strategies for PCOS.